Konsep diri remaja Kristen dalam menghadapi identitiy crisis sosial media - Abraham, Victor; Paulus, Yanto (Sekola Tinggi Teologi Sangkakala Jakarta, 2023)
ABSTRACTAs children of God, youth are endowed with the seeds of Christ's character within. Therefore, in order to grow and maintain the character of Christ in him, he must understand his identity as a follower of Christ. Therefore, Christian youth must provide a real foundation where they will not be influenced by the surrounding influences, especially the influence that is on social media. So that when they enter a period of identity crisis, Christian youth are ready to take their journey to find their identity. The existence of this journal aims to reduce Christian teenagers who experience